Effect of Modified Montmorillonite on the Morphology and Mechanical Properties of Poly(ethyleneterephtalate)/Polyethylene Blends Role of the Polarity and Thermal Stability of the Surfactant - Yousfi, Mohamed; Soulestin, Jeremie; Lacrampe, Marie-France; Vergnes, Bruno (The 27th Annual Meeting of the Polymer Processing Society, 2011)
PET/PE blends were prepared using three different types of commercially available organically modified montmorillonite (OMMT)(Cloisite 15A, 30B and 10A) using conventional polymer melt extrusion process. Characterization of the structure and morphology of nanocomposites obtained is performed using scanning electron microscopy and X-ray diffraction. Mechanical tests of PET/PE/OMMT nanocomposites were analyzed according to the type of organo-modified in nanoclay. It seems that the size of PE nodule phase depends strongly on the chemical structure of the quaternary ammonium surfactant organo-modified of nanoclay. However, the ductility of PET/PE blends depends mainly on the thermal stability of the organoclay. Indeed, a brittle behavior is observed in the presence of C10A probably due to strong surfactant degradation during extrusion process. Then, PET/PE blends were studied prepared using only surfactant those which correspond to (Cloisite 15A, 30B and 10A) to evaluate the effect of the organo modifier without the presence of the monmorillonite lamellae. A decrease in the size of PE droplets was observed wich varies with a trend similar to what found in the presence of clay. It shows unambiguously that the key factor for organoclay compatibilization efficiency of PET/PE blends is the surfactant modifier itself and not the monmorillonite lamellae.
Keywords: Poly(ethylene terephthalate); polyethylene; compatibilization; nanoclay; organic modifier; morphology; mechanical properties; thermal stability